Legal Consequences Due to the Vacancy of Notary Maatschap Implementation Regulation - Vania Syane Gunawan, Irish; Suryono, Arief; Mulyoto, Mulyoto (International Journal of Educational Research & Social Sciences, 2024)
This study aims to analyze: a) the concept of Notary maatschap in Law No. 30 of 2004 concerning the Position of Notary jo Law No. 2 of 2014 concerning the Position of Notary and also according to article 1618 of the Civil Code; b) knowing the legal consequences of the deletion of paragraph (3) of Article 20 of Law No. 2 of 2014 concerning the Position of Notary; c) knowing the basis for the implementation of the Notary maatschap.This research uses normative legal research methods and prescriptive analysis with a statute approach. The legal materials used are primary legal materials and secondary legal materials. The data collection techniques used are literature study, data analysis, description, construction, argumentation, and systematization techniques. The results of this study show that the first regulation Implementation in UUJN is no longer valid based on the principle of lex posterior derogat legi priori. So, the Notary Civil Partnership is based on the Civil Code and Article 20 of the UUJN. However, the provisions of the Civil Partnership of the Civil Code are not relevant if used by the Notary Maatschap. In the absence of clear regulations, the independence of Notary in working is limited because they have to collaborate with allied partners. This impacts the structural, functional, and financial independence of Notaries who previously worked independently. This includes maintaining the confidentiality of deeds. These two Notary Maatschap give rise to multiple interpretations and legal uncertainty, which can then lead to a violation of the Notary's oath of office, so the provisions of Article 20 of UUJN-P should be revoked.